Paracoccus leucadendri Mazzeo & Franco in Mazzeo, Franco & Russo, 2009, a junior synonym of Paracoccus hakeae (Williams, 1985) comb. nov. (Coccomorpha: Pseudococcidae) - Ellenrieder, Natalia Von; Watson, Gillian W.; Kinnee, Scott A.; Franco, José C.; Mazzeo, Gaetana (Zootaxa, 2016)
Two mealybug species (Hemiptera: Coccomorpha: Pseudococcidae) feeding on Proteaceae in U.S.A. (California), Portugal and Australia were studied: Paracoccus leucadendri Mazzeo & Franco in Mazzeo, Franco & Russo, 2009, described from Portugal, and Phenacoccus hakeae Williams, 1985, described from Australia. A comparative morphological analysis was made of relevant paratypes and additional specimens from Australia, California and Portugal, and the variability of the morphological characters in the populations in each country was documented. Molecular analysis of the COI gene of specimens from Australia and California showed them to be identical, and comparative morphological analysis among specimens from Australia, California and Portugal revealed no differences either; therefore Paracoccus leucadendri is placed as a junior synonym of Phenacoccus hakeae. A comparison of the COI sequences with those of species of Paracoccus, Phenacoccus and other mealybug genera revealed that Phenacoccus hakeae does not belong in Phenacoccus. Even though its COI shows no close match to any other species its morphology fits within the generic concept of Paracoccus, and we transfer it to that genus under the new combination Paracoccus hakeae (Williams, 1985) as a holding option until a comprehensive phylogenetic analysis of the group is carried out.